2021
DOI: 10.3389/fendo.2021.774244
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Immune and Stroma Related Prognostic Marker for Invasive Breast Cancer in Tumor Microenvironment: A TCGA Based Study

Abstract: BackgroundBreast cancer (BC) is the most frequent cancer in women. The tumor microenvironment (TME), consisting of blood vessels, immune cells, fibroblasts, and extracellular matrix, plays a pivotal role in tumorigenesis and progression. Increasing evidence has emphasized the importance of TME, especially the immune components, in patients with BC. Nevertheless, we still lack a deep understanding of the correlation between tumor invasion and TME status.MethodsTranscriptome and clinical data were retrieved from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Approximately 40% of patients with ER-positive breast cancer have defects in the DNA repair mechanism, which is an important factor contributing to endocrine resistance in breast cancer. A study revealed that compared to patients with low ERCC1 expression, (30,31). Multivariate regression analysis revealed that vascular tumor thrombus is an independent prognostic factor for patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 40% of patients with ER-positive breast cancer have defects in the DNA repair mechanism, which is an important factor contributing to endocrine resistance in breast cancer. A study revealed that compared to patients with low ERCC1 expression, (30,31). Multivariate regression analysis revealed that vascular tumor thrombus is an independent prognostic factor for patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This increases the risk of lymph node and distant metastasis in patients with breast cancer. Vascular tumor thrombus indicates poor prognosis in patients with breast cancer and can predict distant metastasis and local recurrence of tumors ( 30 , 31 ). Multivariate regression analysis revealed that vascular tumor thrombus is an independent prognostic factor for patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another TCGA analysis that assessed core genes associated with breast cancer status revealed SLAMF6/CD352 as one of eight core genes. However, SLAMF6 had only a weak association with survival (P=0.042) and no significant association with tumor (T), node (N), and metastases (M) (TNM) status and was not further assessed ( 20 ).…”
Section: Slamf Receptors In Solid Tumorsmentioning
confidence: 99%
“…Approximately 1 decade ago, immune infiltration in the TME was observed as a prognostic factor that should not be ignored [9]. According to recent research, tumor-infiltrating immune cells (TICs) and stromal components play an important role in the development of breast cancer [10,11], colorectal cancer [12], and cutaneous melanoma [13].…”
Section: Introductionmentioning
confidence: 99%